New data on the endangered Chacoan peccary (Catagonus wagneri) link the core distribution with its recently discovered southern population - Torres, Ricardo (2018)
The endangered Chacoan peccary (Catagonus wagneri Rusconi, 1930) has been recorded in western Paraguay, southeastern Bolivia and northern Argentina, reaching the north of Santiago del Estero province. Recently, however, this species was found much further south in central Argentina, ca. 650 km away from the southern limit of its known distribution. In this report we provide new records in previously unsurveyed areas linking the core range with the southern population, suggesting a continuous distribution. Due to synergistic effects of hunting pressure and deforestation, we are almost certain that the Chacoan peccary is as threatened in central Argentina as in the rest of its distribution range.